The Role of Parents' Interpersonal Communication in Accompanying Children with use Gadgets - Huda, Nurul; Aristawati, Evy; Cahyono, Bagus Dwi (Global Health Science Group, 2024)
Children are God's gift in marriage. Child development is the responsibility of parents. During the current development period, children will face increasingly modern times with increasingly sophisticated technology with the use of gadgets, this condition has an impact on changes in activities where they spend more time playing with gadgets. Regarding the use of gadgets by children, the role of parents is important to see this as the background and formulation of the problem created is